Cabo Verde : Third Review Under the Policy Coordination Instrument-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2021)
The Cabo Verdean economy is in recession as a result of the economic impact of the pandemic that has shut down the tourism and transport sectors and significantly affected the rest of the economy. The number of COVID-19 cases continues to rise with concentration in the largest island, though the recovery rate is high. The economic outlook remains highly uncertain and dependent upon the duration of the pandemic, the global economic recovery, and the authorities' ability to support the expected economic recovery through the appropriate policies and reforms. Legislative and presidential elections are scheduled for April and October, respectively.